2022
DOI: 10.1111/jog.15215
|View full text |Cite
|
Sign up to set email alerts
|

Fertility‐sparing surgery for early‐stage cervical cancer: A case series study on the efficacy and feasibility of cervical conization followed by pelvic lymphadenectomy

Abstract: Objectives To evaluate the oncologic and obstetric outcomes of cervical conization followed by pelvic lymphadenectomy, which is used as a fertility‐sparing procedure, in reproductive‐aged patients with early‐stage cervical cancer. Methods We performed a retrospective study of patients with stage IA1–IB1 cervical cancer who underwent cervical conization followed by pelvic lymphadenectomy from 2011 to 2020 at Kumamoto University Hospital. Results In total, eight patients underwent conization followed by pelvic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Multiple studies investigated the results of fertility-sparing treatment in the early stages of cervical cancer and considered the subsequent pregnancies and their outcomes [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Anderson et al (2018) studied the pregnancy rate in women with a history of previous cancer and compared it to that of women from the general population ( Table 1 ) [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies investigated the results of fertility-sparing treatment in the early stages of cervical cancer and considered the subsequent pregnancies and their outcomes [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Anderson et al (2018) studied the pregnancy rate in women with a history of previous cancer and compared it to that of women from the general population ( Table 1 ) [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…After removing 129 duplicate studies, the remaining 389 articles were screened based on titles and abstracts, and obviously ineligible articles were excluded, resulting in a total of 148 articles remaining. After reading the full texts, 17 studies that met the study criteria were eventually included in the analysis (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The specific search process are detailed in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Among them, 138 women gave birth to at least one healthy baby. The combined live birth rate was 33.9% (95% CI, 0.261-0.422) (17)(18)(19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), and the heterogeneity test result for the included studies was I 2 = 63.2 P < 0.05, indicating high heterogeneity among the included studies (Figure 5-1). Subgroup analysis showed no significant difference among subgroups.…”
Section: Live Birth Rate and Miscarriage Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Absence of residual disease in the cervix was of great importance. There were some clinical trials recently which showed that cervical conization with lymph node evaluation may be a feasible conservation management in low-risk cervical cancer [ 29 , 30 ]. Negative surgical margin (> 3 mm) after conization could be oncologic safe even in fertility-sparing patients with stage IB1 (≤ 2 cm).…”
Section: Discussionmentioning
confidence: 99%